ANALISIS KOMUNIKASI PEMBINAAN SEBAGAI UPAYA MENJAGA MOTIVASI ATLET KARATE KATA DALAM PERSIAPAN PEKAN OLAHRAGA NASIONAL - Sabda Nugraha, Detrina; Ratri Rahmiaji, Lintang; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study aims to analyze coaching communication in maintaining karate kata athletes' motivation in preparation for the National Sports Week (PON). Communication between coaches and athletes is a key element in sports coaching, especially in motivating athletes to achieve their best performance. Using a qualitative approach, this study collected data through in-depth interviews with coaches and athletes and direct observation during training sessions. The results showed that effective communication, including providing constructive feedback, emotional support, and setting clear goals, played a significant role in maintaining and improving athlete motivation. In addition, communication strategies that are personalized and tailored to the needs of individual athletes have been shown to reduce stress and increase their self-confidence. This study emphasizes the importance of the role of coaching communication in achieving success in prestigious competitions such as PON, and provides practical recommendations for coaches in optimizing communication with their athletes.